2023
DOI: 10.3390/ijms24021091
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Has the Liver Been Spared?

Abstract: The liver is a secondary and often collateral target of COVID-19 disease but can lead to important consequences. COVID-19 might directly cause a high number of complications in patients with pre-existing chronic liver disease, increasing their risk of hepatic decompensation. Moreover, it also determines indirect consequences in the management of patients with liver disease, especially in those suffering from decompensated cirrhosis and HCC, as well as in the execution of their follow-up and the availability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 223 publications
0
4
0
Order By: Relevance
“…All areas of HCC management [ 13 ] were impacted, with the suspension of surveillance programs and reduced access to surgical and interventional radiology for cancer treatment, alongside a recommendation that oral tyrosine kinase inhibitors could be considered for all stages of HCC, given that the tablets could be delivered by courier, alleviating the need and risk of attending hospital [ 14 , 15 ]. These changes reflect the rapid reorganisation of hospital activities to minimise patient exposure to SARS-CoV-2 as much as possible, whilst maintaining clinical outcomes [ 16 ]. Adoption of guidance regarding kinase inhibitors was confirmed by our study, with these prescribed across all BCLC stages, with no delays seen in the delivery of systemic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…All areas of HCC management [ 13 ] were impacted, with the suspension of surveillance programs and reduced access to surgical and interventional radiology for cancer treatment, alongside a recommendation that oral tyrosine kinase inhibitors could be considered for all stages of HCC, given that the tablets could be delivered by courier, alleviating the need and risk of attending hospital [ 14 , 15 ]. These changes reflect the rapid reorganisation of hospital activities to minimise patient exposure to SARS-CoV-2 as much as possible, whilst maintaining clinical outcomes [ 16 ]. Adoption of guidance regarding kinase inhibitors was confirmed by our study, with these prescribed across all BCLC stages, with no delays seen in the delivery of systemic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the number of investigations dedicated to this problem is highly limited, so further explorations are required [228,229]. Nevertheless, the analysis of individuals with non-cirrhotic CLD indicated ALD as the state predisposing to increased mortality [230,231].…”
Section: Alc and Sars-cov-2-any Specific Patterns And Relationships?mentioning
confidence: 99%
“…COVID-19 may increase the risk of hepatic decompensation by directly causing many complications in patients with CLD. Furthermore, it also affects indirect outcomes in the management of patients with CLD, particularly in those having decompensated cirrhosis and HCC [ 109 ]. Patients with cirrhosis have an increased risk of liver decompensation and acute-on-chronic liver failure (ACLF) following viral infection, such as influenza [ 110 ].…”
Section: Sars-cov-2 Infection In Special Populations With Cldmentioning
confidence: 99%
“…Historic trials have revealed a >30-fold increase in ACE2 expression in cirrhotic vs. healthy livers, indicating that cirrhotic patients can be uniquely susceptible to COVID-19-related hepatic dysfunction [ 26 ]. Taking all data into account, patients with CLD are not at high risk of COVID-19, but these patients are at high risk of mortality [ 109 ].…”
Section: Sars-cov-2 Infection In Special Populations With Cldmentioning
confidence: 99%